2019
DOI: 10.1111/anae.14691
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxaemia during recovery after surgery for colorectal cancer: a prospective observational study

Abstract: Episodic and ongoing hypoxaemia are well-described after surgery, but, to date, no studies have investigated the occurrence of episodic hypoxaemia following minimally-invasive colorectal surgery performed in an enhanced recovery setting. We aimed to describe the occurrence of postoperative hypoxaemia after minimally-invasive surgery in an enhanced recovery setting, and the association with morphine use, incision site, fluid intake and troponin increase. We performed a prospective observational study of 85 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 44 publications
3
23
2
Order By: Relevance
“…Hypoxaemia is a potential life-threatening yet common complication after surgery. In observational studies, hypoxaemia was reported in 21-55% of patients during the initial 48 postoperative hours [1,2], and was reported even after mini-invasive surgery [3]. Routine use of supplemental oxygen does not prevent hypoxaemic episodes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxaemia is a potential life-threatening yet common complication after surgery. In observational studies, hypoxaemia was reported in 21-55% of patients during the initial 48 postoperative hours [1,2], and was reported even after mini-invasive surgery [3]. Routine use of supplemental oxygen does not prevent hypoxaemic episodes [2].…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that there were 11 (13.0%) and 4 (4.7%) patients with a troponin I concentration of more than 15 ng.l −1 and 45 ng.l −1 , respectively. The authors also mentioned a cut‐off level of 45 ng.l −1 for ischaemia, therefore, the significance of an elevated level less than 45 ng.l −1 appears questionable.…”
mentioning
confidence: 97%
“…Bojesen et al. recently demonstrated significant associations between postoperative increases in troponin I and the time patients spent with an oxygen saturation of 88% or below, and hypopnoea episodes. However, there appeared to be no correlation between the time patients spent with an oxygen saturation below 88% and morphine use, fluid intake, complications or incision site in 85 patients undergoing minimally invasive surgery for colorectal cancers in an enhanced recovery setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Sun et al. for their interest in our paper regarding postoperative hypoxaemia after minimally invasive colorectal cancer surgery . They raise several clinically important questions; whether using an increase in troponin level below the cut‐off of ischaemia is questionable; the appropriate precautions to take to prevent hypoxaemia and steps to take when encountering elevated troponin levels; the association between complications and hypoxaemia; and the association of hypoxaemia with haemoglobin levels, blood loss and obesity.…”
mentioning
confidence: 99%